SiN-SOI multilayer platform for prospective applications at 2 μm - Sia, Brian Jia Xu (2021)
Silicon photonics at the 2 μm waveband, specifically the 1.9 μm wavelength region is strategically imperative. This is due to its infrastructural compatibility (i.e., thulium-doped fiber amplifier, hollow-core photonic bandgap fiber) in enabling communications, as well as its potential to enable a wide range of applications. While the conventional Silicon-on-Insulator platform permits passive/active functionalities, it requires stringent processing due to high-index contrast. On the other hand, SiN can serve to reduce waveguiding losses via its moderate-index contrast. In this work, by demonstrating SiN passives and Si-SiN interlayer coupler with favorable performance, we extend the Si-SiN platform to the 1.9 μm wavelength region. We report waveguide propagation loss of 2.32 dB/cm. Following, trends in radiation loss with regards to bending radius is analyzed. A high performance 3-dB power splitter with insertion loss and bandwidth of 0.05 dB and 55 nm (1935 - 1990 nm) respectively is introduced. Lastly, Si-SiN transition loss as low as 0.04 dB is demonstrated.